Amelioration of Fibrotic Remodeling of Human 3-Dimensional Full-Thickness Skin by Transglutamase 2 Inhibition - Zhou, Xiang; Trinh-Minh, Thuong; Matei, Alexandru-Emil; Györfi, Andrea Hermina; Hong, Xuezhi; Bergmann, Christina; Schett, Georg; Atkinson, John; Bowcutt, Rowann; Patel, Jessal; Johnson, Timothy S.; Distler, Jörg H.W. (Arthritis and Rheumatology, 2023)
Objective: Fibrotic tissues are characterized by excessive crosslinking between extracellular matrix (ECM) proteins, rendering them more resistant to degradation. Although increased crosslinking of ECM is thought to play an important role for progression of tissue fibrosis, enhanced ECM crosslinking has not yet been targeted therapeutically in systemic sclerosis (SSc). Here, we investigated the role of transglutaminase 2 (TG2), a central crosslinking enzyme, in the activation of SSc fibroblasts. Methods: We assessed TG2 expression and activity using TG2 staining, Western blotting, and TG2 activity assays. We inhibited TG2 in fibroblasts cultured under standard 2-dimensional conditions and in a 3-dimensional full-thickness equivalent skin model using monoclonal inhibitory anti-TG2 antibodies. Results: TG2 expression was increased in the skin of patients with SSc compared with healthy controls, with levels particularly high in patients with SSc-associated interstitial lung disease. TG2 expression and TG2 activity were also increased in SSc dermal fibroblasts. Moreover, the levels of circulating TG2 in the plasma samples from SSc patients were increased versus samples from healthy controls. Anti-TG2 antibodies did not show consistent antifibrotic effects across different fibroblast cell lines under 2-dimensional culture conditions; however, anti-TG2 antibodies effectively reduced transforming growth factor β–induced dermal thickening, myofibroblast differentiation, and collagen accumulation in the 3-dimensional full-thickness model of human skin. Conclusion: We provide the first evidence, to our knowledge, that inhibition of TG2 might be a potential antifibrotic approach in SSc. Our findings have translational potential as anti-TG2 antibodies are currently evaluated in a phase II clinical trial in chronic allograft injury and would thus be available for clinical studies in SSc (ClinicalTrials.gov identifier: NCT04335578). (Figure presented.).
CRIS-Team Scopus Importer:2023-07-21